2016
DOI: 10.1007/s13762-016-0987-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different phases of bismuth silicate nanofibers for photodegradation of organic dyes

Abstract: Two different phases of bismuth silicate nanofibers [Bi 2 SiO 5 and Bi 4 (SiO 4 ) 3 ] were synthesized using electrospinning technique. BS nanofibers were tested for the photocatalytic degradation of methyl orange and safranin O dyes. Different phases of BS affect the photodegradation efficiency of nanofibers. Impressive enhancement in photocatalytic efficiency and BET surface area of Bi 4 (SiO 4 ) 3 was observed over Bi 2 SiO 5 . A speedy reduction in dyes concentration was attributed to the rapid formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The whole solution was stirred for about 90 minutes in a capped beaker. The final solution was loaded into a syringe and a voltage of 10 kV was applied between the tip of the needle and collector plate 13,14 . As spun PVP/ bismuth silicate nanofibers were collected on a copper plate.…”
Section: Methodsmentioning
confidence: 99%
“…The whole solution was stirred for about 90 minutes in a capped beaker. The final solution was loaded into a syringe and a voltage of 10 kV was applied between the tip of the needle and collector plate 13,14 . As spun PVP/ bismuth silicate nanofibers were collected on a copper plate.…”
Section: Methodsmentioning
confidence: 99%
“…They focused on the influence of pH and redox potential of electrolyte on the measured results and revealed that the negative flat-band potential increases with the increase in the redox potential of the electrolyte used. Additionally, for electrolytes containing Fe(CN) 6 4− and I − species, the specific adsorption of the anions was found to cause significant changes in Helmholtz potential, thus affecting flat-band potential values [42].…”
Section: Sli State and Processes At Sli For Bso Materials In Two Mediamentioning
confidence: 98%
“…Bismuth silicates (Bi 2 SiO 5 , Bi 12 SiO 20 , Bi 4 Si 3 O 12 , etc.) and their composites seem to be promising photocatalysts [6][7][8][9], which is due to their activity in the visible range [10] and high polarization and internal electric field [11,12], as well as their ability to form effective junctions (S-scheme [13], type-II [14]), and so on. Previously, we obtained bismuth silicate (BSO)-based materials via mechanical activation [15] and laser fragmentation [16].…”
Section: Introductionmentioning
confidence: 99%
“…For photocatalytic activity, the photocatalyst surface area has a signi cant in uence on the degradations of pollutants [1,[38][39][40][41], since the greater surface area has a higher ability to absorb dye pollutants from the solution which consequently increases the reaction rate and enhances the degradation response. The N 2 adsorption-desorption curve was generated from Brunauer-Emmett-Teller (BET) analysis to calculate surface area.…”
Section: Surface Chemistrymentioning
confidence: 99%